2022
DOI: 10.3390/ijms23063276
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogel Supplemented with Metformin Promotes Neuron–like Cell Differentiation of Gingival Mesenchymal Stem Cells

Abstract: Human gingival mesenchymal stem cells (GMSCs) are derived from migratory neural crest stem cells and have the potential to differentiate into neurons. Metformin can inhibit stem–cell aging and promotes the regeneration and development of neurons. In this study, we investigated the potential of metformin as an enhancer on neuronal differentiation of GMSCs in the growth environment of chitosan hydrogel. The crosslinked chitosan/β–glycerophosphate hydrogel can form a perforated microporous structure that is suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Images taken from the freeze-dried hydrogels ( Figure 1 C) revealed that the surface morphology in the CS/PF samples ( Figure 1 C (1)) was compact with the presence of small channels. In contrast, in the CS/PF/BGP hydrogels ( Figure 1 C (2)) an interconnected porous morphology was observed, suggesting that the addition of the gelling agent created micro- and nano-scale pores in the structure [ 35 ]. As previously shown, the gelation time reduced with the addition of BGP because the hydrogen bridge bonds between the CS chains increase and electrostatic interactions arise between BGP phosphate groups and CS amino groups [ 30 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Images taken from the freeze-dried hydrogels ( Figure 1 C) revealed that the surface morphology in the CS/PF samples ( Figure 1 C (1)) was compact with the presence of small channels. In contrast, in the CS/PF/BGP hydrogels ( Figure 1 C (2)) an interconnected porous morphology was observed, suggesting that the addition of the gelling agent created micro- and nano-scale pores in the structure [ 35 ]. As previously shown, the gelation time reduced with the addition of BGP because the hydrogen bridge bonds between the CS chains increase and electrostatic interactions arise between BGP phosphate groups and CS amino groups [ 30 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 1320 cm −1 was attributed to the C-N stretching in the secondary amide (amide III) [ 43 ]. In the BGP spectrum, two intense signals were detected, with one at 1050 cm −1 related to the asymmetric stretching vibrations of the PO 4 3− group (ν 3 ) and the other at 960 cm −1 related to the symmetrical stretching vibrations (ν 1 ) of the same group [ 35 , 42 , 44 ]. There was another band of lower intensity due to the aliphatic stretching of P-O-C [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC NPs were not cytotoxic in a CCK-8 assay. Next, we examined whether metformin could enhance the osteogenic differentiation of BMSCs in chitosan hydrogel growth environments ( Cai et al, 2022 ). Alkaline phosphatase activity in BMSCs was significantly increased after 3 days of treatment with the studied MHC NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between proteome or metabolome changes and drug perturbation was also explored in some of the selected papers. A proteomic snapshot of progressive molecular signatures was carried out in hippocampal mice tissue after pharmacological inhibition of nitric oxide synthase activity [46], whilst a proteomic analysis highlighted the effects of chitosan hydrogel supplemented with metformin on the neural differentiation of stem cells, with the final aim of employing them in the construction of biomimetic scaffolds for disease treatment [47].…”
mentioning
confidence: 99%